Tissue-scale mechanical coupling reduces morphogenetic noise to ensure precision during epithelial folding - Eritano, Anthony; Bromley, Claire L.; Bolea Albero, Antonio; Schütz, Lucas; Wen, Fu-Lai; Takeda, Michiko; Fukaya, Takashi; Sami, Mustafa M.; Shibata, Tatsuo; Lemke, Steffen; Wang, Yu-Chiun (Developmental cell, 2020)
Morphological constancy is universal in developing systems. It is unclear whether precise morphogenesis stems from faithful mechanical interpretation of gene expression patterns. We investigate the formation of the cephalic furrow, an epithelial fold that is precisely positioned with a linear morphology. Fold initiation is specified by a precise genetic code with single-cell row resolution. This positional code activates and spatially confines lateral myosin contractility to induce folding. However, 20% of initiating cells are mis-specified because of fluctuating myosin intensities at the cellular level. Nevertheless, the furrow remains linearly aligned. We find that lateral myosin is planar polarized, integrating contractile membrane interfaces into supracellular “ribbons.” Local reduction of mechanical coupling at the “ribbons” using optogenetics decreases furrow linearity. Furthermore, 3D vertex modeling indicates that polarized, interconnected contractility confers morphological robustness against noise. Thus, tissue-scale mechanical coupling functions as a denoising mechanism to ensure morphogenetic precision despite noisy decoding of positional information.
Gesehen am 14.05.2020